Efficient sequestration of boron from liquid phase by amidoxime-functionalized poly(acrylonitrile-co-acrylic acid) experimental and modelling analyses - Adeyi, Abel Adekanmi (Water science and technology : a journal of the International Association on Water Pollution Research, 2022)
This study aims to produce amidoxime-modified poly(acrylonitrile-co-acrylic acid) using an optimized method and to investigate the performance of amidoxime-modified poly(acrylonitrile-co-acrylic acid) on the adsorption of boron ions in batch operations. Batch adsorption was conducted at the physiochemical parameters of pH, adsorbent dosage, and initial boron concentration. The isotherms and kinetics of adsorption data were studied at various initial boron concentrations. The renewed synthesis process gave a production yield of 77%, and the conversion of nitrile group to amidoxime was 78%. The adsorption reached its optimum point at pH = 8, adsorbent dosage = 4 g·L-1, and initial adsorbent concentration at 40 ppm. The best model fits for isotherm adsorption was the Sips model with heterogeneity factor (n) = 0.7611. In the kinetic study, the adsorption data fitted best with pseudo-second-order model. The synthesized polymeric adsorbent could be recycled with little decline in its boron entrapment capacities. Hence, amidoxime-modified poly(acrylonitrile-co-acrylic acid) exhibited high adsorption capacity and could be potentially explored as an alternative to commercial resin in the removal of boron from wastewater